PENGARUH MODEL CHILDREN LEARNING IN SCIENCE (CLIS) TERHADAP HASIL BELAJAR IPA SISWA KELAS III UPT SPF SD INPRES ANTANG I - Abdullah; Satriawati; Syamsul Alam; A. Alfiani Damayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Children Learning In Science (CLIS) model on the Science Learning Outcomes of Grade III Students of UPT SPF SD Inpres Antang I. This study is a quantitative study with an experimental research type with a pre-experimental one group pretest-posttest design. The sample in this study was 32 grade III students consisting of 17 boys and 11 girls. The sampling technique in this study was saturated sampling. The research instruments used were observation sheets, learning outcome tests, and documentation. Data analysis used descriptive analysis and inferential statistical analysis with the help of the SPSS computer program. The results of this study indicate that teacher activities obtained an average value of 3.4 and student activities obtained an average value of 3.1 which means they were implemented well. The learning outcomes of third-grade students are explained from the results of the prerequisite tests consisting of the results of the pretest normality test of 0.121 < 0.05 which is normally distributed, the results of the homogeneity test of 0.414 < 0.05 which means homogeneous and the results of the hypothesis test of 0.000 with Sig (0.000) < α (0.05). So, the results of this study indicate that there is an influence of the Children Learning In Science (CLIS) model on the learning outcomes of third-grade students at the UPT SPF SD Inpres Antang I.